Threshold space in the context of communal ritual: the kilungan fence and spatial transformation in the Buka Luwur Sunan Kudus tradition - Anisa, Anisa; Purwanto, Edi; Sardjono, Agung Budi; Riskiyanto, Resza (Jurnal Penelitian Saintek, 2026)
Space in the cultural approach and perspective is not only a physical space but also as a meaningful phenomenon. This meaning can be formed through shared experiences and religious-ritual activities. One of the communal rituals that demonstrates the dynamics of unique spaces in the Old City of Kudus is the tradition of Buka Luwur Sunan Kudus. This tradition of Buka Luwur Sunan Kudus is a cultural-religious ritual held once a year in the month of Muharram in the Old City of Kudus. The center of the Buka Luwur activity is in the area of ​​the Mosque, Tajug, and the Tomb of Sunan Kudus. One of the architectural elements that plays a role in the Buka Luwur tradition is the kilungan fence around the center of the activity. This study aims to examine the function of the threshold space in the cultural-religious practices of the Kudus community, analyze the transformation of space during the Buka Luwur tradition, and explain how the concept of space and boundaries become an integral part of communal and spiritual experiences. In accordance with the research objectives, this study uses a post-positivistic paradigm. Data collection was carried out through field observations and interviews during the procession. The results of this study demonstrate that during the Buka Luwur tradition, the kilungan fence not only serves as a boundary but also as a threshold element. The narrow, straight corridor bordered by the tall, massive kilungan fence becomes a threshold space that conveys, mediates, and accompanies spatial experiences. This spatial experience is between everyday space and the temporal sacred space. The kilungan fence, with its long, straight form, binds the Buka Luwur activity and directs movement. The kilungan fence not only plays a physical role but also has a meaningful meaning, symbolizing the path to the sacred center. The results of this study enrich the concept of threshold space, especially when rituals occur within it.